2014
DOI: 10.5812/ircmj.12581
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis Study to Investigate the Prevalence of Helicobacter pylori and the Sensitivity of its Diagnostic Methods in Iran

Abstract: Context:Helicobacter pylori is the most common infecting organism affecting humans, being almost half the population infected. The aim of this study was to find out the epidemiological features and the sensitivity of diagnostic methods of Helicobacter pylori infection in Iran, which can provide the logic of developing preventive approaches to control Helicobacter pylori infections and the associated diseases.Evidence Acquisition:By reviewing the databases of SID, MAGIRAN, SCOPUS, MEDLIB, Google, ISI and PUBMED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…A previous meta-analysis study demonstrated that the prevalence of H. pylori infection in Iran was 50.7% (95% CI, 44.4-56.9) [49]. The frequencies of peptic ulcers and gastric malignancy are highly affected by ethnical and geographical variables; therefore, these findings combined with the lower efforts for H. pylori eradication in Iran as well as a considerable of recurrent infections may indicate a high developmental process of Iranian isolates [11].…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis study demonstrated that the prevalence of H. pylori infection in Iran was 50.7% (95% CI, 44.4-56.9) [49]. The frequencies of peptic ulcers and gastric malignancy are highly affected by ethnical and geographical variables; therefore, these findings combined with the lower efforts for H. pylori eradication in Iran as well as a considerable of recurrent infections may indicate a high developmental process of Iranian isolates [11].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the prevalence among younger generations was low ( 4 ). A review and meta-analytic study showed that the mean prevalence of H. pylori was 50.7% during 1994- 2011 with the lowest and highest prevalence in Tehran (19.2%) and Mazandaran (74.27%) provinces, respectively ( 5 ). A survey in Tehran showed that 87.6% of patients with dyspepsia were infected with H. pylori ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori is a spiral-shaped, Gram-negative, microaerophilic and fastidious bacterium ( 1 , 2 ), and infects almost 50% of the world’s population ( 3 , 4 ). It is the main cause of chronic gastritis, gastric and duodenal ulcers, mucosa-associated lymphoid tissue lymphoma and gastric adenocarcinoma ( 2 , 5 ). In the international agency for research on cancer (IARC), H. pylori has introduced as a first class (definitive) carcinogen ( 6 ).…”
Section: Introductionmentioning
confidence: 99%